2022
DOI: 10.1080/20008066.2022.2137913
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of adverse childhood experiences among Chinese preschool parents and the intergenerational transmission of risk to offspring behavioural problems: moderating by coparenting quality

Abstract: Background: Although intergenerational transmission of ACEs among parents and their offspring have been extensively studied in the West, few studies have been conducted in China on preschool children and their parents, and explore the protective fact for the intergeneration transmission. Objective: Using latent class analysis and moderation model, this study examined the associations between patterns of adverse childhood experiences of Chinese preschool parents and behavioura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…The gross domestic product (GDP) of Anhui province in 2020 was CNY 3,868.1 billion, representing moderate level in China (National Bureau of Statistics of China, 2021 ). The detail of study design and participants also can be found in our previous study (Zhu et al, 2022 ). Of the total sample, the average age of mothers were 34.38 years (SD = 4.89).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gross domestic product (GDP) of Anhui province in 2020 was CNY 3,868.1 billion, representing moderate level in China (National Bureau of Statistics of China, 2021 ). The detail of study design and participants also can be found in our previous study (Zhu et al, 2022 ). Of the total sample, the average age of mothers were 34.38 years (SD = 4.89).…”
Section: Methodsmentioning
confidence: 99%
“…Child age (months), child sex (1 = male, 2 = female), mother’s age (years), and family socioeconomic status (SES) were included as covariates (Zhu et al, 2022 ). Five indicators were used for SES: father and mother’s occupation, education level, and family income.…”
Section: Methodsmentioning
confidence: 99%
“…The majority of reports on the questionnaire were completed by the preschoolers’ mothers (76.5%), while others were reported by fathers (22.8%) and other relatives (0.7%). The preschoolers’ annual family income ranged from below ¥50 k to above ¥300 k, with an average income between ¥100 k and ¥150 k; 95.3% of the families received 50,000 yuan per year as their family income, which showed the economic level of our sample was higher than the Chinese average poor family income level [ 24 ]. Table 1 shows the descriptive statistics for all study variables.…”
Section: Methodsmentioning
confidence: 99%
“…The SES consisted of five indicators: the father’s occupation, education level, the mother’s occupation, education level, and the family’s annual income. The average standardized score of five indicators was calculated as the family SES in our study [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Adverse childhood experiences (ACEs) do not have a single cause, it takes on several causes and forms, as many factors contribute to ACEs, ranging from parents, family environments, personality traits, socioeconomic circumstances, the school, peers, mental health issues, physical health problems, to community/neighborhood characteristics [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. The crux is ACEs facilitate, simulate, and play significant roles in the maltreatment and trauma of ACEs' victims' lives [3,4,7,10,12,16,17].…”
Section: Introductionmentioning
confidence: 99%